Project-Based Learning (PjBL) Worksheet on the Production of Whey Kefir Paper Soap - Islamiati, Fitri Nur (JTK (Jurnal Tadris Kimiya), 2023)
Students often ask about the practical application of concepts and knowledge gained from their coursework. Practicum worksheets provide an opportunity for students to engage in hands-on learning, identify their strengths, learn from their mistakes, and develop enhanced competence as learners. This study aims to develop an effective and valid worksheet on PjBL in whey kefir paper soap. Research and Development (R&D) is used as a method. Worksheet designs were produced using three formulas depending on production techniques. Based on Indonesia National Standard, Formula 1 (8% whey kefir) demonstrated the best qualities of the paper soap. The expert validation test of the worksheets showed a rcount value of 0.84 (valid). The percentage of worksheet answers was very good (88%). Student worksheet feasibility test results showed a rcount value of 0.84 (feasible). Practicum worksheets are categorized as very suitable for use as a learning media in an organic chemistry course.